Influence of Supercritical CO2 on the Formation Sensitivity of Tight Sandstone - Peng, Huan; Zhou, Lang; Yang, Jian; Peng, Junliang; Han, Huifen; Gou, Xinghao; Wang, Zhouyang (Frontiers in Energy Research, 2022)
It's challenging to get water-based fracture fluid to flow back in low-pressure gas reservoirs. In order to solve the problem, supercritical CO2 is a novel type of non-aqueous fracturing technique with a wide range of applications prospect in low-pressure tight sandstone. To determine whether supercritical CO2 fracturing with low pressure tight sandstone is feasible. Tight sandstone cores from the Jinqiu Gas field in the Sichuan Basin were used to evaluate the influence of supercritical CO2 on the formation sensitivity of sandstone reservoirs. Supercritical CO2 was used to interact with tight sandstone samples under formation conditions, and then the changes in velocity sensitivity, water sensitivity, salinity sensitivity, alkaline sensitivity, acid sensitivity, and stress sensitivity of tight sandstone were observed. Velocity sensitivity damage decreased by 5.4%, water sensitivity damage decreased by 13.3%, salinity sensitivity damage decreased by 16.6%, alkaline sensitivity damage decreased by 2%, acid sensitivity damage decreased by 14.4%, and stress sensitivity damage increased by 8% after the interaction between tight sandstone and supercritical CO2. This finding provides a quantitative assessment of the impact of supercritical CO2 on formation sensitivity, and it can be used to build a supercritical CO2 fracturing scheme for low-pressure water sensitive tight sandstone.